Study on the influence mechanism of hole sizes on the mechanical properties and damage laws of sandstone - Hou, Fubin; Wang, Hanpeng; Sun, Dekang; Zhou, Yuguo; Zhang, Bing; Wang, Wei; Zhang, Jinhou; Wu, Yunhao (Theoretical and applied fracture mechanics, 2026)
•Uniaxial compression-DIC-GDEM integration studies borehole size effects on sandstone.•Real-time monitoring captures H → X → S strain field evolution and failure patterns.•Critical threshold η = 0.085–0.141 dominates boundary-effect deviations enabling new rock instability approaches. To prevent and control rock bursts in deep coal mines, the optimization of the geometric parameters of antiscour and pressure relief drilling is highly important for adjusting the stability of the surrounding rock. Therefore, through uniaxial compression tests, GDEM numerical simulations, DIC strain monitoring and other methods, the mechanical properties and damage laws of sandstone samples with different pore sizes are systematically studied. The crack propagation mode and strain field evolution law are discussed in depth, and the influence mechanism of the boundary effect under different pore sizes is analyzed. The results show that with increasing pore size, the uniaxial compressive strength decreases in the form of a quadratic function, and the number of sudden changes in the dissipated energy conversion rate and the peak value decrease gradually. The failure mode changes from an oblique linear shear failure to an S-type tensile shear failure, and the strain field morphology in the early stable loading stage changes from H-type to X-type and then S-type. Owing to the boundary effect, the theoretical and experimental results have different degrees of matching at φ = 0°, and the measured change trend of the key point strain value is basically consistent with the theoretical values. At φ = 26.75°, when η ranges from 0.085 to 0.141, the measured value exhibits a regular decrease, which subsequently changes to a rapid increase, which is quite different from the theoretical results. This study provides a theoretical basis for exploring the stability and catastrophic evolution trends of surrounding rock in deep engineering scenarios.